THE EFFECT OF INVESTMENT OPPORTUNITY SET ON DIVIDEND POLICY WITH LIQUIDITY AS MODERATING VARIABLE: Study of Trading, Service and Investment Sector Companies Listed on the Indonesia Stock Exchange for the 2014-2019 Period - Martha Fadliana, Fikri; Khaerunnisa, Enis (Management Science Research Journal, 2024)
This study aims to determine the effect of investment opportunity set proxied by MVEBVE (market to book value of equity) on dividend policy proxied by DPR (dividend payout ratio) with liquidity proxied by CR (current ratio) as a moderating variable in trading, service and investment sector companies listed on the Indonesia Stock Exchange for the 2014-2019 period. The population used is all trading, service and investment sector companies listed on the IDX for the period 2014 to 2019, totaling 109 companies. The sample collection method used in this study was purposive sampling and obtained 13 companies as samples. The analysis technique used is descriptive statistical analysis, classical assumption test, hypothesis testing, and moderated regression analysis (MRA) carried out using the help of IBM SPSS 22.0 software. Based on the results of the analysis, it is known that: (1) Investment opportunity set has no positive effect on dividend policy. (2) Liquidity is not able to moderate the relationship between investment opportunity sets on dividend policy.